Pathologie und Molekularpathologie des Peniskarzinoms - Fiegl, August; Hartmann, Arndt; Junker, Kerstin; Mink, Jan; Stöhr, Robert (Die Pathologie, 2025)
Penile carcinoma exhibits significant geographic variation in incidence, ranking 30th globally among newly diagnosed cancers with an annual rate of 0.84 cases per 100,000 men. Particularly high incidence rates of up to 2.2 are seen in Latin America, Asia, and Africa, largely due to a high prevalence of HPV, lower circumcision rates, and inadequate hygiene standards.The 2022 WHO classification of urogenital tumors continues to differentiate penile carcinomas based on their HPV status; however, the subdivision of numerous subtypes especially of the HPV(+) carcinomas was abandoned. This article aims to present current knowledge on the carcinogenesis of HPV(+) and HPV(-) penile carcinomas and their precursor lesions as well as updates from the latest WHO classification.Approximately 50% of penile carcinomas are caused by infection with high-risk HPV subtypes, with positive p16 immunohistochemistry serving as a good surrogate marker for HPV(+) tumors. HPV(-) carcinomas frequently show TP53 mutations and are associated with a poorer prognosis.While localized penile carcinomas have a relatively good prognosis, survival rates in metastatic cases remain poor. Neither microsatellite instability nor mismatch-repair deficiency appear to play a role, but up to 62.2% of tumors express PD-L1. Currently, immune checkpoint inhibitors such as Avelumab and Ipilimumab, along with antibody-drug conjugates targeting TROP2 and Nectin‑4, are being tested in clinical trials, potentially leading to the approval of targeted therapies for metastatic penile carcinoma in the future.
EVALuna2:578181